2010
DOI: 10.1002/adma.200903896
|View full text |Cite
|
Sign up to set email alerts
|

NixCo3−xO4 Nanowire Arrays for Electrocatalytic Oxygen Evolution

Abstract: NixCo3−xO4 nanowire arrays are grown on a Ti foil for efficient oxygen evolution reactions. Ni‐doped nanowire arrays have higher electrocatalytic activity than pure Co3O4. The success of the nanowire electrodes results from their high surface areas and direct electron contact to the conductive substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
616
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 865 publications
(644 citation statements)
references
References 19 publications
24
616
0
4
Order By: Relevance
“…Apart from the noble metal‐based electrocatalysts, recently earth‐abundant electrocatalysts have attracted much attention in water oxidation reaction 130, 147. Ni‐doped Ni x Co 3–x O 4 nanowire arrays with large surface area and efficient charge transfer have been demonstrated to be superior over their nanoparticle film equivalents in electrocatalytic OER.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…Apart from the noble metal‐based electrocatalysts, recently earth‐abundant electrocatalysts have attracted much attention in water oxidation reaction 130, 147. Ni‐doped Ni x Co 3–x O 4 nanowire arrays with large surface area and efficient charge transfer have been demonstrated to be superior over their nanoparticle film equivalents in electrocatalytic OER.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…One of the earliest examples of using 1D Co 3 O 4 nanowires for OER was reported in 2010,26 in which the synthesis of mesoporous Ni x Co 3–x O 4 nanowire arrays was first achieved on the surface of Ti foils via an ammonia evaporation induced growth. Spectroscopic characterizations indicated that the Ni element had an uneven distribution and was concentrated on the nanowire surface.…”
Section: Oermentioning
confidence: 99%
“…Among different types of morphologies and structures, the one‐dimensional (1D) nanoscale materials have been demonstrated as one unique target for serving excellent electrocatalyst candidates ( Figure 2 ). 26, 27, 28 First, these 1D materials have high surface areas, large roughness factors and high active‐site densities, which are beneficial for providing efficient catalytic activity for surface electrochemical reactions. Second, the 1D materials can provide channels and few crystal boundaries for fast charge transport pathways with reduced scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Besides enthusiastic efforts to search for new electrocatalysts to facilitate these processes, numerous studies are also devoted to making better use of the existing electrocatalysts for achieving optimal properties 2, 8, 9, 10, 11. Common strategies for enhancing the performances of electrocatalysts include either optimization of their chemical compositions or micro/nanostructures 2, 8, 9, 10, 11. Nevertheless, these methods require complicated procedures with long‐time operation and the catalytic performances remain unsatisfactory.…”
mentioning
confidence: 99%
“…Conventional catalyst electrodes are prepared by depositing active species, such as platinum, copper, titanium, nickel, etc., on the surface of 2D or 3D metallic supports 10, 11, 27. Because of the general incompatibility between electrocatalysts and these supports, the active species are vulnerable to peeling off during elongated catalysis duration (Figures S10 and S11, Supporting Information).…”
mentioning
confidence: 99%